OPTIMIZING IRON ABSORPTION IN CHILDREN THROUGH VITAMIN C SUPPLEMENTATION AND FORTIFICATION: A REVIEW - Aulia, Bianda; Notarianti, Rizna; Larasati, Adisti; Sitorus, Nova Lidia (Journal of Indonesian Specialized Nutrition, 2025)
Background: Iron deficiency aeamia is common in children, particularly in low- and middle-income countries, where diets are typically low in bioavailable iron and infections are prevalent. As vitamin C enhances non-heme iron absorption, this review explores current evidence on its role in improving iron status in children. Methods: A narrative literature review was conducted using PubMed, Scopus, and Google Scholar and included studies published from January 2000 to June 2025. Search terms combined keywords related to “vitamin C”, “iron absorption”, “supplementation”, “fortification”, “children”, and “anemia”. Results: Iron absorption in children is influenced by iron form, dietary factors, and developmental stage, with infants and young children at greatest risk of deficiency. Vitamin C is an enhancer of non-heme iron absorption, counteracting inhibitors such as phytates and calcium. Trials combining oral iron with vitamin C supplementation generally showed greater increases in hemoglobin and ferritin compared with iron alone, particularly among children with iron deficiency. Evidence from fortification studies is limited and varies due to differences in study design. Conclusion: Vitamin C co-supplementation might improve iron status in children. However, existing evidence remains insufficient to support specific recommendations for children.